Influencia del proceso de enseñanza-aprendizaje de la natación en los alumnos del octavo año de educación general básica jornada vespertina del colegio nacional nueve de octubre de la ciudad de Machala periodo lectivo 2013-2014 - Aguirre Murgueitio, Edgar Javier (2014)
Present Titling Project Influence of Teaching-Learning Process swimming in the eighth year students of Basic General Education afternoon session of the National College October 9 city of Machala Teaching period 2013-2014 is the bathroom An investigative work, diagnosed and proactive aimed at identifying aquatic activities that currently used by teachers of the National School Nueve de Octubre in the Teaching-Learning Process of eighth Year Basic Education in general.